ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Efendi, Bogi Hilman; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The research was purposed to analyzed the financial performance of the company before and after doing merger and acquisitoins. Which was the independent variables of thie research were merger and acquisiton, and the dependent variable was financial performance. The sampel that used for this research was secondary data from merged and acquisition company’s financial report. The Sampling technique that used was purposive sampling with certain criterias which according to the purpose of this research. The steps to analyzed the data was counted data from financial report’s balance sheet, loss and profit report used financial ratio with time series analysis metodh which compared time and period and compared it with industry average standard, with the purpose so that it can be shown in the graphic.the Financial Ratio included Net Profit Margin Ratio, Return on Equality, Debt to equality Ratio, total Asset Turn over and current ratio. Results of the research can be concluded that the merged and aqcusiton’s company value of the financial ratio of the sampled companies increased and decreased compared to rfinancial ratio a year before merged and acquisiton. Value of the analyzed ratio still below the standard of industry average.Keywords: Financial performance, mergers and acquisitions